ANALISA PSIKOLOGI HUBUNGAN INTERPERSONAL DALAM FILM “KTP” - Heni Nur Achdiyah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Abstract The film entitled “KTP” is a short film that has a unique and interesting story. The story in this film sparks conversation and discussion because it highlights bureaucratic problems and the relationship between the community and state officials. The phenomenon of culture and social relations in real everyday life is the background of the film that makes us feel part of the story. Socio-cultural dynamics are reflected in the storyline. Mbah Karsono and Darno are the main characters and get attention. This article aims to analyze the short film “KTP” from the point of view of the psychology of interpersonal relationships. Judging from several theories of interpersonal relations Many social interactions occur in this film, resulting in various dynamics of interpersonal relationships. The conflict shown in this film creates a feeling of dilemma. But managed to resolve at the end of the story. Keywords: film analysis, interpersonal relations, psychological perspective